2019
DOI: 10.1128/mra.00520-19
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Genome Sequence of a Fusarium xylarioides Race Pathogenic to Robusta Coffee ( Coffea canephora ) in Uganda

Abstract: Here, we report the first whole-genome assembly of a Fusarium xylarioides race pathogenic to robusta coffee in Uganda. It comprises 55,122,624 bases and 14,552 genes. Gene ontology analysis assigned 5,720 genes to biological processes, 4,545 genes to cellular components, and 6,021 genes to molecular function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…Previous work described the pathology of the epidemics (Flood 2009), clarified molecular taxonomy (Buddie et al 2015, Flood 2005, showed reproductive isolation between the host-specialists (Lepoint et al 2005), and reported the first genome (Olal et al 2019). The genetic basis for successive outbreaks and host-specialisation remains unexplored, however.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work described the pathology of the epidemics (Flood 2009), clarified molecular taxonomy (Buddie et al 2015, Flood 2005, showed reproductive isolation between the host-specialists (Lepoint et al 2005), and reported the first genome (Olal et al 2019). The genetic basis for successive outbreaks and host-specialisation remains unexplored, however.…”
Section: Introductionmentioning
confidence: 99%
“…Each F. xylarioides MEGAHIT assembly from this study, as well as those assembled previously [26] and the publicly available genomes robusta925 [89] and robustaL0394 [90], were mapped to the reference genome assembly.…”
Section: Methodsmentioning
confidence: 99%
“…Single nucleotide polymorphisms (SNPs) were called against the arabica563 reference genome for each set of F. xylarioides reads. Reads for robusta925 were downloaded from the Sequence Read Archive (accession PRJNA508603, [89]) and robustaL0394 were shared by [90].…”
Section: Methodsmentioning
confidence: 99%